Abstract book of the XII RUSSIAN SCIENTIFIC CONFERENCE IN OZONE-THERAPY (Ozone Therapy Global Journal, 2022)
XII RUSSIAN SCIENTIFIC CONFERENCE IN OZONE-THERAPYV INTERNATIONAL JOINT CONFERENCE RUSSIAN-IMEOFOzone: active forms of oxygen, nitric oxide, molecular hydrogen,and high-intensity physical factors in biology and medicineNizhny Novgorod, October 14-15, 2021